2018
DOI: 10.1136/bjsports-2017-098903
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise interventions reduce blood pressure in patients after stroke or transient ischaemic attack: a systematic review and meta-analysis

Abstract: . (2018). Aerobic exercise interventions reduce blood pressure in patients after stroke or transient ischaemic attack: a systematic review and meta-analysis. British Journal of Sports Medicine. Copyright and re-use policy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 61 publications
2
58
0
2
Order By: Relevance
“…While the novice did receive training and benefited from a pilot period, others who have used the CERT have reported no difficulties in using the Explanation and Elaboration Statement and Checklist. 54,55 Completeness of reporting has been investigated for the CONSORT Statement [56][57][58][59][60] and the TIDieR Checklist. 7,56 Inter-rater reliability has not been routinely evaluated for reporting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…While the novice did receive training and benefited from a pilot period, others who have used the CERT have reported no difficulties in using the Explanation and Elaboration Statement and Checklist. 54,55 Completeness of reporting has been investigated for the CONSORT Statement [56][57][58][59][60] and the TIDieR Checklist. 7,56 Inter-rater reliability has not been routinely evaluated for reporting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…23,55,56 Importantly, the behavior change platform is relevant in the context of evidence-based interventions designed to encourage the adoption of compensatory cognitive strategies 57,58 and other pro-cognitive behaviors such as aerobic exercise. 59…”
Section: Sar As a Model For Carmentioning
confidence: 99%
“…Furthermore, they did not include any other vascular or metabolic risk factors besides SBP and DBP [13]. The review of Wang et al [12] reported a significant result of combined aerobic training and resistance exercises on both systolic blood pressure (À4.30 mmHg, 95% CI À6.77 to À1.83) and diastolic blood pressure (À2.58 mmHg, 95% CI À4.71 to À0.46). The review of D'Isabella et al did find significant effects of exercise training both with and without lifestyle coaching.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have addressed exercise as secondary prevention after stroke. These reviews all included studies in which the intervention existed of a combination of aerobic training with strength exercise and/or lifestyle interventions [12][13][14][15]. D'Isabella et al found that combined aerobic training and strength exercise has a risk reducing effect on several vascular risk factors after stroke [15].…”
Section: Introductionmentioning
confidence: 99%